Identification of Licopyranocoumarin and Glycyrurol from Herbal Medicines as Neuroprotective Compounds for Parkinson's Disease - Fujimaki, Takahiro (Public Library of Science, 2014)
In the course of screening for the anti-Parkinsonian drugs from a library of traditional herbal medicines, we found that the extracts of choi-joki-to and daio-kanzo-to protected cells from MPP(+)-induced cell death. Because choi-joki-to and daio-kanzo-to commonly contain the genus Glycyrrhiza, we isolated licopyranocoumarin (LPC) and glycyrurol (GCR) as potent neuroprotective principals from Glycyrrhiza. LPC and GCR markedly blocked MPP(+)-induced neuronal PC12D cell death and disappearance of mitochondrial membrane potential, which were mediated by JNK. LPC and GCR inhibited MPP(+)-induced JNK activation through the suppression of reactive oxygen species (ROS) generation, thereby inhibiting MPP(+)-induced neuronal PC12D cell death. These results indicated that LPC and GCR derived from choi-joki-to and daio-kanzo-to would be promising drug leads for PD treatment in the future.